2014
DOI: 10.1093/ageing/afu010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multimodal exercise on cognitive and physical functioning and brain-derived neurotrophic factor in older women: a randomised controlled trial

Abstract: Australian and New Zealand Clinical Trial Registration Number: ANZCTR12612000451808.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
1
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(184 citation statements)
references
References 23 publications
5
158
1
15
Order By: Relevance
“…This is supported by data showing that BDNF peripheral levels may increase after physical exercise (Schmolesky et al 2013;Vaughan et al 2014). In addition, it was demonstrated that the increase in BDNF after physical training correlates with improvements in cognitive functions in aged non pathological subjects (Vaughan et al 2014) as well as in patients affected by pathological conditions such as stroke (El-Tamawy et al 2014) and depression (Pereira et al 2013;Oral et al 2012). …”
Section: Introductionmentioning
confidence: 63%
“…This is supported by data showing that BDNF peripheral levels may increase after physical exercise (Schmolesky et al 2013;Vaughan et al 2014). In addition, it was demonstrated that the increase in BDNF after physical training correlates with improvements in cognitive functions in aged non pathological subjects (Vaughan et al 2014) as well as in patients affected by pathological conditions such as stroke (El-Tamawy et al 2014) and depression (Pereira et al 2013;Oral et al 2012). …”
Section: Introductionmentioning
confidence: 63%
“…Exercise encourages neuron formation, grey matter and brain-derived neurotrophin factor (BDNF), a protein that keeps neurons alive and increases the growth of neurons and synapses in the area of the hippocampus where new information is stored. Vaughan, Wallis, Polit et al (2014) found that football improved cardio-vascular and muscular-skeletal fitness and affected aspects of brain function that are important for performance in competitive situations demanding skill and judgement. Krustrup, Aagaard, Nybo et al (2010) found that small-sided football produced high aerobic activity with mean heart rates of 80-85% of age-related maxima.…”
Section: Introductionmentioning
confidence: 99%
“…Combined exercise training (CET) has demonstrated to be effective in increasing physical fitness and cognition (Vaughan et al 2014). Nutritional therapy, such as supplementation with taurine, can also decrease inflammation in several pathological conditions (Marcinkiewicz and Kontny 2014).…”
Section: Introductionmentioning
confidence: 99%